The Concept Of “Ahl Al-Sunnah Wa Al-Jamā‘Ah” Revisited - Baharudin Abdul Rahman (Ma'had Aly Idrisiyyah, 2022)
Understanding about the meaning of “Ahl al-Sunnah wa al-Jamā‘ah” in the hadith which reads: